Incidence of curable sexually transmissible infections among adolescents and young adults in remote Australian Aboriginal communities: analysis of longitudinal clinical service data. (4th November 2014) - Silver, Bronwyn J; Guy, Rebecca J; Wand, Handan; Ward, James; Rumbold, Alice R; Fairley, Christopher K; Donovan, Basil; Maher, Lisa; Dyda, Amalie; Garton, Linda; Hengel, Belinda; Knox, Janet; et al.
Abstract : Objectives: To undertake the first comprehensive analysis of the incidence of three curable sexually transmissible infections (STIs) within remote Australian Aboriginal populations and provide a basis for developing new control initiatives. Methods: We obtained all results for Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG) and Trichomonas vaginalis (TV) testing conducted during 2009–2011 in individuals aged ≥16 years attending 65 primary health services across central and northern Australia. Baseline prevalence and incidence of all three infections was calculated by sex and age group. Results: A total of 17 849 individuals were tested over 35 months. Baseline prevalence was 11.1%, 9.5% and 17.6% for CT, NG and TV, respectively. During the study period, 7171, 7439 and 4946 initially negative individuals had a repeat test for CT, NG and TV, respectively; these were followed for 6852, 6981 and 6621 person-years and 651 CT, 609 NG and 486 TV incident cases were detected. Incidence of all three STIs was highest in 16-year-olds to 19-year-olds compared with 35+ year olds (incident rate ratio: CT 10.9; NG 11.9; TV 2.5). In the youngest age group there were 23.4 new CT infections per 100 person-years for men and 29.2 for women; and 26.1 and 23.4 new NG infections per 100 person-years in men and women, respectively. TV incidence in this age group for women was also high, at 19.8 per 100 person-years but was much lower in men at 3.6 per 100 person-years. Conclusions: This study, the largest ever reported on the age and sex specific incidence of any one of these three curable infections, has identified extremely high rates of new infection in young people. Sexual health is a priority for remote communities, but will clearly need new approaches, at least intensification of existing approaches, if a reduction in rates is to be achieved.